A Survey to Assess the Prevalence of Stress and Stressors among Medical Students - Mohi Ud Din, Komal Ahsan, Warda Aslam, Umer Siddique, Sana Majeed, Aizaz Mujahid, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Stress has an effect on the cognitive performance of medical students, which leads to poor health and burnout. Aim: To figure out how much stress medical students perceive and what the likely stressors are. Methods: This cross-sectional study was conducted in medical colleges of Faisalabad. Study duration was 4 months (October 2021 to January 2022). A sample size of 380 was taken. The inclusion criteria included medical undergraduate students and who gave consent while those who didn’t give the consent and who were not medical students were excluded.Non-probability convenient sampling technique was used for collection of study participants. Data was collected from medical students. Time required to complete the questionnaire was 5 - 10 min. A questionnaire titled “The Perceived Stress Scale (14 items)” was used. Results: Majority of the students were having moderate stress. The mean perceived stress score of participants was 29.79±5.3. Mean perceived stress score of males and females was 29.56±5.41 and 29.94±5.18 respectively. Class 2nd year MBBS showed the highest mean of perceived stress score as 31.79±6.39 than other classes. Also, younger age group perceived more stress. Among the stressors, academic and psychosocial stressors played significant role as compared to environmental stressors. Conclusion: The perceived stress is higher among younger age group, class 2nd year MBBS students and females. Academic and psychosocial stressors were more common in participants than environmental. Personal and institutional initiatives are urgently required to keep medical students from becoming distressed. Medical students must be taught coping mechanisms and self-care practices. It is critical to underline that, in complement to teaching students, it is also critical to consider the students' well-being during their years of medical study. These things can be applied to community as well and with help of this study, their stress factors can be assessed and coping mechanisms can be advised. Keywords: Academic, psychological, medical, prevalence, students, stress, stressors